Dressed to kill - Neill, Roy William, 1887-1946; Rathbone, Basil, 1892-1967; Bruce, Nigel, 1895-1953; Doyle, Arthur Conan, 1859-1930.; Universal Pictures Company; Cinetel Films ([North Hollywood, CA] : Universal Pictures Company, Inc., 1946)
Pitted once again against a treacherous female adversary, Holmes and Watson set out to find a group of bank plates stolen from the Bank of England. The fate of Britain's international finance rests on the sleuths' shoulders, as they brush dangerously close to death. The key to the mystery lies in three identical musical boxes which were accidentally sold at auction. But the heinous conspirators stop at nothing to get the boxes back--with only Holmes to stop it.
Based on a story by Arthur Conan Doyle.
Basil Rathbone, Nigel Bruce, Patricia Morison.
Cinematographer, Maury Gertsman; editor, Saul A. Goodkind; musical director, Milton Rosen.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Thieves -- England -- Drama; Bank robberies -- England -- Drama; Holmes, Sherlock -- Drama; Detective and mystery films; Film adaptations; Internet videos; Fiction films; Feature films; Streaming video